Pengaruh Pemberian Jahe Merah Terhadap Penurunan Nyeri Disminorea Pada Remaja Putri Kelas X di SMA Al-Azhar 3 Bandar Lampung - Cahya, Yuwika; Susilawati, Susilawati; Utami, Vida Wira; Hermawan, Dessy (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT Dysmenorrhea is abdominal pain originating from uterine cramps that occurs during menstruation. The prevalence of dysmenorrhea, according to the World Health Organization (WHO) (2013), is approximately 1,769,425 individuals. The global incidence of dysmenorrhea is about 50% of women experiencing dysmenorrhea. In Indonesia, according to the Ministry of Health of the Republic of Indonesia 2016, indicates that around 55% of adolescents experience dysmenorrhea. This study aims to determine the effect of consuming a red ginger beverage on 10th grade female students at SMA Al-Azhar 3 Bandar Lampung who experience dysmenorrhea. This was a quantitative research study using a pre-experimental method with a one-group pretest-posttest design. The population of this study consisted of 92 10th-grade female students at SMA Al-Azhar 3 Bandar Lampung, and the sample consisted of 21 female students who experienced dysmenorrhea. Data analysis involved univariate and bivariate analyses using the Wilcoxon test. The average dysmenorrhea pain among female students before consuming the red ginger beverage on the first day was 43.33. On the third day of measurement after consuming the red ginger beverage, the dysmenorrhea pain among female students decreased to an average of 4.29. The Wilcoxon statistical test yielded a p-value of 0.000 (<0.05), indicating that there was an effect of consuming red ginger beverages on reducing dysmenorrhea pain among 10th-grade female students at SMA Al-Azhar 3 Bandar Lampung in 2023.Conclusion: It is recommended that female students experiencing dysmenorrhea consider consuming a red ginger beverage as an alternative to reduce dysmenorrhea pain. Keywords: Dysmenorrhea, Red Ginger, Female Students  ABSTRAK Dismenorea adalah nyeri perut yang berasal dari kram rahim dan terjadi selama menstruasi. Prevalensi dismenore menurut World Health Organization (WHO) tahun 2018 angka dismenore di dunia sangat besar, rata rata lebih dari 50% perempuan disetiap negara (Puspita, 2018) dan sekitar 10-15% diantaranya mengalami dismenore berat (Apriyanti, dkk, 2018). Di Indonesia sendiri, angka kejadian dismenore menurut Kementerian Kesehatan RI (2016) menunjukkan bahwa sekitar 55% remaja mengalami dismenore. Mengaetahui pengaruh pemberian minuman jahe merah pada remaja putri kelas X di SMA Al-Azhar 3 Bandar Lampung. Jenis penelitian kuantitatif, dengan metode pra ekpeimental dengan pendekatan one group pretest-postest design, populasi dalam penelitian ini berjumlah 92 siswi kelas X di SMA Al-Azhar 3 Bandar Lampung dan siswi yang mengalami nyeri disminorea sebanyak 21 siswi. Analisa data univariat dan bivariat menggunakan uji Wilcoxon. Rata-rata nyeri disminorea remaja putri sebelum diberikan minuman jahe merah pada hari pertama dengan mean 43,33. Pada hari ketiga pengukuran setelah diberikan minuman jahe merah nyeri disminorea remaja putri mengalami penurunan dengan mean 4,29. Hasil uji statistic Wilcoxon di dapat nilai p-value 0,000 (<0,05) yang artinya terdapat pengaruh pemberian minuman jahe merah terhadap penurunan nyeri disminorea kelas X di SMA Al-Azhar 3 Bandar Lampung Tahun 2023. Diharapkan remaja putri yang mengalami nyeri disminorea dapat mengonsumsi minuman jahe merah sebagai alternatif untuk mengurangi nyeri disminorea. Kata Kunci: Disminorea, Jahe Merah, Remaja Putri